Bridging cultural and developmental approaches to psychology new syntheses in theory, research, and policy - Jensen, Lene Arnett (New York ; Oxford : Oxford University Press, 2011)
This cutting-edge book brings together eminent experts who propose ways to bridge cultural and developmental approaches to human psychology. The experts heed the call of cultural psychology to study different peoples around the world and to recognize that culture profoundly impacts how we think, feel, and act.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 10, 2011).
Keywords: Developmental psychology; Developmental psychology -- Social aspects